PELATIHAN PEMBUATAN SEDIAAN PERMEN SIRSAT SEBAGAI ANTIOKSIDAN SEBAGAI DAYA TAHAN TUBUH DI WILAYAH KERTEN LAWEYAN SURAKARTA: PELATIHAN PEMBUATAN SEDIAAN PERMEN SIRSAT SEBAGAI ANTIOKSIDAN SEBAGAI DAYA TAHAN TUBUH DI WILAYAH KERTEN LAWEYAN SURAKARTA - Vivin Nopiyanti; Reslely Harjanti; Siti Aisiyah; Titik Sunarni; Suhartinah Suhartinah; Ilham Kuncahyo (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
Soursop fruit contains vitamin C and polyphenolic compounds that have the potential as a source of antioxidants. It is hoped that by consuming a lot of soursop fruit it will provide an increase in memory and to maintain cell damage due to free radicals. Making soursop candy preparations will allow use which is relatively easy to use and gives a good taste so that not only adults consume it but also for children. Service activities are divided into several stages starting from surveys and observations, followed by training in the form of tutorials then mentoring from the service team and ending with activity evaluation. Making soursop candy preparations is easy, simple and uses simple tools. We often encounter soursop fruit in the yard and for additional materials for making soursop preparations, it is easy to find on the market and the price is cheap. The principle of making it is all the ingredients are boiled until it becomes a semi-solid dough. Then wait until it cools down. Once cool, cut according to taste and wrapped in an attractive wrapper. Service activities carried out in RT 1/RW 1, Laweyan District, Surakarta went well while still implementing health protocols. In addition to providing training on making soursop candy preparations for PKK cadres in Kerten Laweyan Surakarta, training was also held related to opportunities to be developed as community independent businesses. The conclusion of the activity and evaluation of the preparation of soursop candy is considered to have the potential to be developed so that it can be used as an independent business product that is marketed commercially.